The new genus Magnacrus (Araneae: Theraphosidae: Ornithoctoninae) from Vietnam, with notes on Citharognathus hosei Pocock, 1895 - Hoang, Quang Duy; Yu, Kun; Wendt, Ingo; West, Rick C.; Wirth, Volker Von (Zootaxa, 2025)
A new ornithoctonine genus, Magnacrus gen. nov., is established with two species from the Central Highlands of Vietnam. Magnacrus tongmianensis (Zhu, Li & Song, 2002) gen. nov. comb. nov. is transferred from Citharognathus Pocock, 1895, and is redescribed based on the new Vietnamese specimens; its type locality is potentially wrongly recorded, this species likely does not inhabit China. A new species, M. taynguyenensis gen. nov. sp. nov., from Vietnam is described with both sexes. The type species of Citharognathus, C. hosei Pocock, 1895, is redescribed based on the type specimen and new samples from two populations of Sarawak, Borneo. The males of M. tongmianensis gen. nov. comb. nov., and C. hosei are additionally described. Insights into natural history and conservation of all species are included. A distribution map for both Magnacrus species is provided.